Why things matter to people : social science, values and ethical life - Sayer, R. Andrew (Cambridge, UK : Cambridge University Press, 2011)
'Andrew Sayer undertakes a fundamental critique of social science's difficulties in acknowledging that people's relation to the world is one of concern. As sentient beings, capable of flourishing and suffering, and particularly vulnerable to how others treat us, our view of the world is substantially evaluative. Yet modernist ways of thinking encourage the common but extraordinary belief that values are beyond reason, and merely subjective or matters of convention, with little or nothing to do with the kind of beings people are, the quality of their social relations, their material circumstances or well-being. The author shows how social theory and philosophy need to change to reflect the complexity of everyday ethical concerns and the importance people attach to dignity. He argues for a robustly critical social science that explains and evaluates social life from the standpoint of human flourishing'--
'This book is about social science's difficulties in acknowledging that people's relation to the world is one of concern. When we ask a friend how they are, they might reply in any number of ways, for example:'I'm OK, thanks: my daughter's enjoying school, things are good at home and we've just had a great holiday.''Not so good: the boss is always in a bad mood and I'm worried about losing my job.''OK myself but I'm really appalled by what's been happening in the war.''I'm a bit depressed: I don't know where my life is going.' Such responses indicate that things matter to people, and make a difference to'how they are'. Their lives can go well or badly, and their sense of well-being depends at least in part on how these other things that they care about - significant others, practices, objects, political causes - are faring, and on how others are treating them'--
Introduction: a relation to the world of concern -- Values within reason -- Reason beyond rationality: values and practical reason -- Beings for whom things matter -- Understanding the ethical dimension of life -- Dignity -- Critical social science and its rationales -- Implications for social science -- Appendix: comments on philosophical theories of ethics.
Includes bibliographical references (p. 264-278) and index.
Keywords: Social values; Social norms; Values; Normativity (Ethics).; Social sciences -- Moral and ethical aspects